1978
DOI: 10.1111/j.1460-2466.1978.tb01580.x
|View full text |Cite
|
Sign up to set email alerts
|

Women as TV Experts: The Voice of Authority?

Abstract: Three-yeax study shows more women experts selling products for women but still backed up b y the "known quantity" of an authoritative male uoice-over.This study concerns the attribution of expertise to the women who appear in TV commercials and the roles they portray. An analysis of how women are represented in TV commercials is important for several reasons. It has been contended that TV commercials promulgate sex-role stereotypes and insult and exploit women. Negative images of women in commercials may be po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 5 publications
3
19
0
Order By: Relevance
“…This subject was raised by research suggesting that individuals shown in "head/shoulders only" photos may be rated as more competent than individuals whose full bodies are presented (Schwarz and Kurz 1989). Content analyses of television advertisements have shown that men are frequently presented in roles of authority and competency (Marecek et al 1978;McArthur and Resko 1975). Consequently, it was of interest to ascertain whether competency-associated images were used in sole-male magazine advertisements.…”
Section: Body Portions and Objectification Of Sole-male Imagesmentioning
confidence: 98%
“…This subject was raised by research suggesting that individuals shown in "head/shoulders only" photos may be rated as more competent than individuals whose full bodies are presented (Schwarz and Kurz 1989). Content analyses of television advertisements have shown that men are frequently presented in roles of authority and competency (Marecek et al 1978;McArthur and Resko 1975). Consequently, it was of interest to ascertain whether competency-associated images were used in sole-male magazine advertisements.…”
Section: Body Portions and Objectification Of Sole-male Imagesmentioning
confidence: 98%
“…Although such guides have been available for at least a decade, the continued evidence of sex stereotypes in many communication media suggests limited application. Gender bias has been documented in media as diverse as magazine fiction (Lazar & Dier, 1978), television commercials (Maracek, et al, 1978), speeches of presidential candidates (Purnell, 1978), Sunday comics (Brabant & Mooney, 1986), popular music (Cooper, 1985), introductory college textbooks (Bertilson, et al, 1982), and corporate annual reports (Kuiper, 1986).…”
Section: Literature Reviewmentioning
confidence: 99%
“…H5: Female leads will appear in home-based settings more often than will male leads in television advertisements in both countries (Livingstone and Green 1986;Manstead and McCulloch 1981). H6: Male voice-overs will be more prevalent in television advertisements than will female voice-overs both countries (see Furnham and Bitar 1993;Furnham and Mak 1999;Lovdal 1989;Maracek et al 1978). H7: Women will appear as leads more often than men will in advertisements for household and personal hygiene products in both countries (Thoveron 1987).…”
Section: Introductionmentioning
confidence: 96%